2016
DOI: 10.1177/0363546516652619
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Articular Cartilage Defects With Microfracture and Autologous Matrix-Induced Chondrogenesis Leads to Extensive Subchondral Bone Cyst Formation in a Sheep Model

Abstract: The potential of microfracture technique to induce subchondral bone pathology should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 53 publications
3
40
0
1
Order By: Relevance
“…Experts hypothesize that subchondral bone cyst formation may be caused by an influx of synovial fluid in subarticular bone, resulting in a localized increase in synovial fluid pressure and cytokine-induced, osteoclast-mediated bone resorption. 16,17 The senior author believes that these subchondral changes can be minimized by drilling the lesion rather than using an awl, avoiding confluence of the drill holes, and avoiding postoperative loading of the newly prepared lesion for at least 6 weeks. Conceptually, if the patient loads the freshly prepared lesion, the bone responds similar to fracture repair, including bone overgrowth and sclerotic changes.…”
Section: Complicationsmentioning
confidence: 99%
“…Experts hypothesize that subchondral bone cyst formation may be caused by an influx of synovial fluid in subarticular bone, resulting in a localized increase in synovial fluid pressure and cytokine-induced, osteoclast-mediated bone resorption. 16,17 The senior author believes that these subchondral changes can be minimized by drilling the lesion rather than using an awl, avoiding confluence of the drill holes, and avoiding postoperative loading of the newly prepared lesion for at least 6 weeks. Conceptually, if the patient loads the freshly prepared lesion, the bone responds similar to fracture repair, including bone overgrowth and sclerotic changes.…”
Section: Complicationsmentioning
confidence: 99%
“…Although the AMIC procedure seems to have a beneficial effect on OCLs of the talus, diverse results of microfracture and AMIC use have been presented. In a sheep model, Beck et al (27) used a different collagen membrane and showed bone cyst formation after microfracturing with a communication present between the drilling holes and the cysts. Another study, by Zhang et al (28), demonstrated with a short-term follow-up period that the clinical symptoms had significantly improved.…”
Section: Amic Microfracturing Osteochondral Defects Osteochondrosis Dmentioning
confidence: 99%
“…Auch wurde bei diesen Patienten im Vergleich zu solchen ohne vermehrte Knochenbildung ein 10-fach höheres Versagensrisiko (p < 0,01) beobachtet [76]. Die zusätzliche Verwendung einer abdeckenden Kollagenmembran nach MFx hat bisher weder im Tierversuch noch beim Menschen die überwiegende Entstehung von Faserknorpel oder auch die Bildung intraläsionaler Osteophyten verhindern können [45,77,78].…”
Section: Biologische Erkenntnisse Und Allgemeine Aspekte Zu Verschiedunclassified